Mobile robot path planning: a multicriteria approach - Fernandez, Juan A.; Gonzalez, J.; Mandow, L.; Pérez-de-la-Cruz, J.L. (Engineering applications of artificial intelligence, 1999)
This paper addresses the problem of searching paths in a graph-based model of the environment for mobile robot navigation. Unlike conventional approaches, where just a scalar cost (or a scalar function combining several costs) is to be optimized, this paper proposes a multicriteria path planner that provides an efficient and natural way of both defining and solving problems in which conflicting criteria are involved. In particular, the multicriteria METAL-A ∗ algorithm is used as the core of a mobile robot global path planner. This algorithm has been implemented and tested in the RAM-2 mobile robot for indoor navigation. The results presented demonstrate the performance of the algorithm when dealing with energy-consumption, temporal, and clearance restrictions on the paths.